Lying, Spying, Sabotaging – Balancing Means and Aims – - Nadine Chlaß; Gerhard Riener (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We study individuals who can nudge themselves out of, or opt into a set of rules which either allows them to spy on an opponent, or to sabotage an opponent, or to fabricate payoff-relevant information on the opponent s moves. In an experiment, we observe significant altruism under rules which allow for fabrication and sabotage, but not under rules which allow for spying. We provide direct evidence that this altruism emanates from an ethical concern about the rules of the game. How individuals deal with this concern whether they prefer to nudge themselves into fabrication-free, spying-free, or sabotage-free rules, or whether they assume the power to fabricate or sabotage to compensate their opponent for the rules of the game by giving all payoff away varies along with individuals attitudes toward power.
Keywords: D02; D63; D64; 330